Ecotourism: a harmonious journey with nature - Mamadiyorova Kamola (DEVELOPMENT OF EDUCATION AND SCIENCE IN THE ERA OF DIGITAL TRANSFORMATION, 2025)
Ecotourism is a form of responsible and sustainable travel that serves to strengthen harmony between humans and nature and aims to reduce environmental harm. This article analyzes the role of ecotourism in the development of ecological conservation, support for local communities and cultural understanding. In contrast to mass tourism, ecotourism encourages small-scale, environmentally friendly trips and encourages tourists to preserve nature. Based on the experience of different states, the article will cover the benefits and problems of ecotourism. In particular, the positive effects of this direction in maintaining biodiversity, serving sustainable development, activating the local population and increasing environmental awareness are demonstrated. At the same time, there is also a focus on risks such as" green advertising " (greenwashing) and irregular development.